Overexpression of the Kiwifruit Transcription Factor AaMYB44 Decreases the Cold Tolerance in Arabidopsis thaliana - Yihang Li; Miaomiao Lin; Qina Zhang; Peng Zhang; Zhenzhen Zhang; Yukuo Li; Leiming Sun; Sumei Li; Congcong Li; Dixin Chen; Xiujuan Qi (Plants)
Cold stress is one of the main abiotic stresses that affect the development and growth of kiwifruit (Actinidia arguta). Herein, we analyzed the transcriptomic data of A. arguta dormant shoots in response to low-temperature treatment, identified 52 MYB genes, and constructed a phylogenetic tree based on the encoded protein sequences. Then, the effect of one MYB gene on cold tolerance was analyzed. This gene had an open reading frame of 837 bp long and encoded 279 amino acids. Sequence alignment and phylogenetic analysis revealed that this gene belongs to the R2R3-MYB family and was named AaMYB44 based on its homology to other MYB family members. Quantitative real-time PCR revealed that AaMYB44 expression was significantly induced by low temperatures but exhibited the opposite trend in cold-tolerant genotypes. Subcellular localization assays revealed the nuclear localization of the AaMYB44 protein. Furthermore, AaMYB44 was transformed into Arabidopsis thaliana (A. thaliana) via inflorescence infection, and physiological and biochemical tests revealed that the cold resistance and antioxidant capacity of the transgenic A. thaliana were lower than those of wild-type plants. Overall, AaMYB44 might play a negative regulatory role in response to cold stress, providing new insight into the mechanism of cold tolerance.